Evaluation practices of classroom teachers in health instruction in the elementary schools in the division of Agusan del Norte - Bravo, Concepcion (Ducusin) 1918- (s.n.], 1972)
This paper analyzed the practices of classroom teachers in health instruction in the elementary schools of the Division of Agusan del Norte. Taken as a whole, this study aimed to inspire administrators, supervisors and classroom teachers concerned to plan and work together for a meaningful and successful health instruction program through the use of improved evaluation practices and techniques.